Hydrological Ecosystem Service Assessment Projections in Karst Regions under Future Climate and Land Use Change - Niu Shuai; Yecui Hu; Yuping Bai; Ke Xu; Rong Wang (Ecosystem Health and Sustainability)
Assessing the impacts of future land use cover change (LUCC) and climate change (CC) on hydrological ecosystem services (HESs) is important for regional hydrological ecosystem protection and management. However, the current understanding of the combined effects of CC and LUCC on HESs remains insufficient, especially in the ecologically fragile karst regions. Based on this, this study takes a typical karst region as the study area, and based on the shared socioeconomic pathway (SSP) and representative concentration pathway (RCP) scenarios, the system dynamics (SD) model and the patch-generation land use model (PLUS) are used to simulate the future land use changes, and the spatial and temporal dynamics of the key HESs, such as water yield (WY), soil conservation (SC), and water purification (WP), are assessed. Results indicate that (a) under SSP126, WY and WP increase remarkably in the southeast and northwest, while SC improves in the southwest; however, under SSP585, SC declines and WP exhibits only limited improvement. (b) Synergistic relationships are observed between WY and WP across all scenarios, while trade-offs between SC and other services vary by scale, being more pronounced at the raster level and less so at the watershed scale. (c) Finally, ecosystem service bundles are used to define hydro-ecological management zones at multiple scales, informing adaptive water management strategies. These findings provide valuable insights into dynamic HES prediction and zonal management, offering practical guidance for managing water resources and conserving ecosystems in karst regions.